Genetic Profile and Clinical Implications of Hepatoblastoma and Neuroblastoma Coexistence in a Child - Skoczen, Szymon; Stepien, Konrad; Krzysztofik, Marta; Luszawska, Teresa; Hnatko-Kolacz, Malgorzata; Korostynski, Michal; Piechota, Marcin; Kolanek, Katarzyna; Wyrobek, Lukasz; Wysocka, Katarzyna; Gorecki, Wojciech; Balwierz, Walentyna (Frontiers in Oncology, 2019)
The aim of the following case report is to provide a description of the coexistence of two independent tumors in a child. A 9-month-old male was referred to Department of Pediatric Oncology and Hematology with hepatic tumor present on ultrasound imaging and symptoms of enlarged abdominal circumference. Physical examination revealed a palpable epigastric mass and the imaging techniques showed a tumor of the left hepatic lobe measuring 11 x 6.5 x 8.9 cm with pancreas infiltration, distant metastases in both lungs and abnormal lesion in the left adrenal gland. Basing on histopathological examination, after a core-needle biopsy, hepatoblastoma (HBL) (mixed epithelial-mesenchymal subtype) was diagnosed. The α-fetoprotein level was 112 993 ng/ml. Elevated values of normetanephrine, 3-methoxytyramine as well as neuron-specific enolase were observed. Due to the clinical picture and diagnosis, the patient was qualified to preoperative chemotherapy according to the SIOPEL-3 protocol, followed by SIOPEL-4 protocol for the high-risk patients. After undergoing preoperative chemotherapy, imaging tests revealed regression of hepatic tumor and no focal pulmonary masses, while regression of adrenal gland mass was not completed. The patient was qualified for left hemihepatectomy with left adrenalectomy. Histopathological examination of liver specimen confirmed the HBL diagnosis. However, in left adrenal gland and paraaortic lymph nodes the residual neuroblastoma (NBL) cells were detected. Whole exome sequencing (WES) was utilized to identify disease-associated germline mutations. WES revealed a novel germline insertion variant in TWIST1 (p.Gly86dup), along with the potentially pathogenic nonsynonymous variants in NF1 (p.Val2511Ile), RAF1 (p.Leu445Arg) and WHSC1 (p.Ser4Asn) genes. Currently, 6 months after completion of treatment according to the SIOPEL-4 protocol, the patient is in good general condition, without any signs and symptoms of relapse of both neoplasms. The coexistence of two different primary childhood malignancies is rarely seen. So far, only one case of synchronous HBL and NBL has been reported. However, for the first time therapeutic process was successful. A specific signature of rare germline mutations can be proposed as a predisposing factor to synchronous HBL and NBL occurrence.